Nurcholis Madjid’s Concept of Education (An Analysis of The Concept of Education Curriculum Development In Pesantren) - muhammad Fazlurrahman Hadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Abstract: The Islamic boarding (Pesantren) education curriculum is a tool to achieve the objectives of Islamic Education. Decreasing of students' morallity, equal learning opportunities, low internal efficiency of the education system, institutional status, management of education that is not in line with national development, and unprofessional human resources. The problem faced by pesantren in this era is the narrowing of the curriculum which study of the sciences only grammatically such as: nahwu-sharaf, fiqh, aqa'id, tasawuf, tafsir, hadith, and Arabic. In this context, education curriculum in Pesantren needs to be reformulated including its vision and objectives as well as develop the curriculum. The application of the curriculum in Pesantren needs to be checked and balanced including the balance of classical Islamic repertoire, Islamic knowledge, and general knowledge. Santri (students in Islamic boarding school) can study these sciences not only grammatically, but how to master the sciences verbally or text. So, products (santri) are not only as consumers but producers. Thus, this article is intended to explore Nurcholis Madjid’s concept of the education curriculum in pesantren. Meanwhile, the reason why this thesis is only focused on studying the concept of a e certain figure is because Nurcholis Madjid is a prominent Indonesian Islamic intellectualist who is credible to investigate the reality of the world of education in pesantren. Keywords: Curriculum and Education, Pesantren (Islamic Boarding Schools)